Change of consumers preferences and behavior due to the influence of Covid-19 - Blažek Wijsman, Anežka; Karlíček, Miroslav, 1979-; Kottika, Efthymia, 1982-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2021)
The purpose of this thesis is to examine the changes in Czech consumers' preferences and behaviour due to the influence of Covid-19. The study was conducted using a qualitative research technique. The respondent study pool consisted of great variety of consumers regarding age, demographic location, education level and more. In total, 23 in-depth interviews were conducted. Based on our results, multiple areas of findings emerged. Firstly, the research suggests that Czech consumers engaged in hoarding behaviour depending on their life experience and stress levels. An increase for higher quality and local products was observed. Attitudes towards creating savings changed and long-term trends among the younger generation consist mainly of discovery of home cooking. Furthermore, how does the media influence the Czech consumers perception was detected. Lastly a possible development of online shopping was foreshadowed. These findings are divided into Maslow’s motivation model for better clarity.
Vedoucí práce: Miroslav Karlíček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses